The occurrences of Mg-hydroxycarbonates in serpentinites of the western section of the South Aegean volcanic arc (West Attica peninsula-Northeastern Argolis peninsula), Greece - Stamatakis, M. G.; Mitsis, I. (Bulletin of the Geological Society of Greece, 2013)
In the area of West Attica Peninsula, Greece, ophiolitic rocks which outcrop mainly at the Geraneia Mountains, overlie Triassic-Jurassic limestone and covered by Plio - Pleistocene sedimentary rocks. The relatively widespread ophiolite occurrences are mainly serpentinized peridotites, considered as spinel lherzolites and dunites. In the Northeastern Argolis Peninsula several small remnants of an ophiolitic nappe outcrop which consists from serpentinized and tectonically deformed peridotites, overthrusted on the Eocene flysch. Both regions are characterized by manifestations of volcanic activity. Recently, white mineral aggregates have been discovered in several places in highly altered and serpentinized ultrabasic rocks of the above regions, with the form of irregular accumulations. The identified minerals are hydromagnesite, which predominates, and also magnesite, huntite, and minerals of pyroaurite group. For the study of the Mg-hydroxycarbonate minerals assemblages and the hosting material, PXRD mineralogical analysis, SEM investigations and SEM-EDS microprobe and chemical analyses has been performed. It is suggested that the origin of the secondary Mg-rich hydroxycarbonates was controlled by the alteration of the ophiolites due to a combining actions of intense hydrothermal activity with CO2 -rich fluids, tectonism, as well as the groundwater chemistry that is characterized by high Mg/Ca ratio and alkaline pH values.